Investigating the effect of different amounts of sulfur and zinc on the seed yield of hybrid Monogerm sugar beet (Shirin cultivar) - Saeed Sadeghzadeh Hemayati; Vodod Saidnia; Ghasem Parmoon (علوم و فناوری بذر ایران)
This study was conducted to investigate the role of application of sulfur and zinc on commercial seed yield of sugar beet Monogerm cultivar in a factorial experiment based on randomized complete block design with three replications. The experimental treatments included sulfur (0, 200, and 400 kg/ha) and zinc (0, 20, and 40 kg/ha). The results showed that the seed yield and commercial seed yield, as well as the interaction effect of sulfur and zinc, has a significant impact on seed yield alone. With the application of 400 kg/ha sulfur, the raw seed yield increased by 17% and the commercial seed yield increased by 54%. The highest raw seed yield (3443 kg/ha) was obtained with the application of 400 kg/ha of sulfur and 40 kg/ha of zinc. The simultaneous application of sulfur and zinc led to an increase in the proportion of oversized seeds and standard seeds, and a decrease in the proportion of undersized seeds. The highest percentage of oversized seeds was obtained with the application of 400 kg/ha of sulfur and 20 kg/ha of zinc, The application of 400 kg/ha of sulfur resulted in a 12% and 6% increase in mechanical and p sulfur improved both the quantitative and qualitative aspects of sugar beet seed production, while zinc did not have much influence and only increased the quantity of seed produced. Under the conditions of this study, the combination of 400 kg/ha of sulfur and 40 kg/ha of zinc was recommended.